Phylogeny of Dynastor and Brassolis butterflies (Lepidoptera: Nymphalidae): a tough nut to crack - Garzón-Orduña, Ivonne J.; Penz, Carla M. (Zootaxa, 2009)
This study examines the phylogenetic relationships among species of the butterfly genera Dynastor and Brassolis using 57 characters from adult morphology and wing coloration. We provide evidence for the monophyly of both genera. The relationships among Dynastor species are well resolved, but we were unable to find informative characters that could resolve the relationships inside Brassolis. We provide diagnoses for Dynastor and Brassolis and all species included in these genera, including illustrations that show geographical variation in wing color. The status of one subspecies is changed to species; Brassolis dinizi d’Almeida, 1956, NEW STATUS.